Self Meaning and Communication Experience Blind Athletes Branch of the Sport of Chess at the Riau National Paralympic Comitte - Hanif Ahda, Muhammad; Mia Pramiswari; Nurul Mustaqimah (JIM - Journal International Multidisciplinary, 2024)
Being an athlete with a disability is not easy because as we know from some people with disabilities still get unfair treatment. The Paralympic Committee, which is the parent sports organization for people with disabilities in Indonesia, fosters all sports activities for the achievements of people with disabilities. The purpose of this study was to determine the communication experience of blind athletes in chess at the Riau National Paralympic Committee. The research method used is qualitative descriptive. The data collection techniques used were observation, interviews and documentation. The researcher uses Alfred Schutz's phenomenological theory with indicators of causal motives, goal motives, meanings and communication experiences. The results of this study show that the formation of self-meaning of blind athletes through the learning process, the efforts they make to be able to motivate themselves to a higher level, their confidence to remain outstanding chess athletes.